Determinants of Demand and Participation by Poultry Farmers in Formal and Informal Credit Markets in Cross River State, Nigeria - Udeme Henrietta Ukpe; Bethel Fidelis Ewung (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
A typical challenge for over 65 percent of the Nigerian population living in rural areas and surviving through agricultural activities is access to credit facilities needed to procure technological inputs that trigger productivity. This has consequently limited the capacity of small and micro agro-enterprises - especially poultry enterprises - to develop. Therefore, this study was undertaken to analyse factors affecting the demand and participation of agro-entrepreneurs, particularly poultry farmers, in formal and informal credit markets in Cross River State, Nigeria. Purposive and random sampling techniques were used to select 295 poultry farmers. Data were collected for the 2022 production cycle using structured questionnaires and interviews, and the results were analysed using a multinomial logit model. The results revealed that socioeconomic and enterprise characteristics such as educational level, gender, farm capacity, poultry training, and household assets were significant factors that influenced the participant's choice of credit institution in the study area. Also, favourable terms, outstanding loans and easier access to loans were the institutional factors that affected credit demand. Training and workshop programmes should be organised by government and corporate financial institutions to encourage participation in credit markets so that the abundant available funds can be efficiently utilised in the production process.